Pengolahan Salak Menjadi Dodol Salak Dan Nilai Tambah Untuk Kesejateraan Masyarakat (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
Salak farmers in South Tapanuli Regency, North Sumatra, face the challenge of low prices during harvest season. To overcome this, they developed salak fruit processing into salak dodol. This step is expected to increase the economic value of their products. The biblical value that can be linked to the solution provided by the farmer group is Genesis 2:15. This verse reflects the value of hard work and human effort to cultivate and maintain natural resources, in line with the salak farmers' efforts in processing salak fruit into salak dodol. This study used a qualitative approach with interviews of salak processing industry employees and analysis of related literature. The processing process involves cleaning, cooking, adding brown sugar and coconut milk, and forming the dough into dodol. The result not only increases economic value, but also provides health benefits. Dodol salak has high economic value, opens local business opportunities, creates jobs, and supports regional economic growth. The product also provides a healthy and delicious food alternative. The positive impact is seen in the improvement of the welfare of the local community, diversification of farmers' income sources, promotion of cultural heritage, and tourist attraction. Processing salak into salak dodol not only increases economic value but also supports the economic growth and welfare of salak farmers, making this practice a sustainable solution.